EFFECT OF INTEGRATED PHOSPHORUS MANAGEMENT ON GROWTH, YIELD ATTRIBUTES AND YIELD OF SUMMER GREEN GRAM (VIGNA RADIATA L.) - D. K. RATHOUR,; A. K. GUPTA,; R. R. CHOUDHARY,; A. C. SADHU, (The Bioscan, 2015)
A field experiment was conducted during summer season of the year 2012. Result revealed that application of 40 kg P2O5 ha-1 from SSP significantly increased growth and yield attributes and seed yield (802 kg/ha)over control but remain at par with application 20 kg P2O5 ha-1 from SSP + PSB inoculation @ 5mL kg-1 seed. The highest nodule dry weight (35 mg/plant), protein content in seed (24.20%) and BCR value 3.31 was recorded with 20 kg P2O5 ha-1 from SSP + PSB followed by 40 kg P2O5 ha-1 from SSP. Which indicate that inoculation of PSB save 50 per cent inorganic phosphorus fertilizer.